2015
DOI: 10.1071/sr14330
|View full text |Cite
|
Sign up to set email alerts
|

Management options for water-repellent soils in Australian dryland agriculture

Abstract: Abstract. Water-repellent ('non-wetting') soils are a major constraint to agricultural production in southern and south-west Australia, affecting >10 Mha of arable sandy soils. The major symptom is dry patches of surface soil, even after substantial rainfall, directly affecting agricultural production through uneven crop and pasture germination, and reduced nutrient availability. In addition, staggered weed germination impedes effective weed control, and delayed crop and pasture germination increases the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 137 publications
(194 reference statements)
1
61
0
Order By: Relevance
“…The WDPT classification is wettable (0–5 s), slight (5–60 s), strong (60–600 s), severe (600–3600 s), and extreme (≥3600 s). The MED concentration was classified using the system of Roper et al (2015). The MED classification is wettable (0 and 3% v/v ethanol), low (3 and 5%), moderate (8.5 and 13%), and very severe (24 and 36%).…”
Section: Methodsmentioning
confidence: 99%
“…The WDPT classification is wettable (0–5 s), slight (5–60 s), strong (60–600 s), severe (600–3600 s), and extreme (≥3600 s). The MED concentration was classified using the system of Roper et al (2015). The MED classification is wettable (0 and 3% v/v ethanol), low (3 and 5%), moderate (8.5 and 13%), and very severe (24 and 36%).…”
Section: Methodsmentioning
confidence: 99%
“…3, 4 and 7), in-dicating the advantages of furrow planting over flat pattern with no zeolite application in dryland farming conditions. Several studies have shown that furrow sowing in dryland conditions has many benefits such as easily shedding of rain from ridges, accumulation of runoff in furrows, infiltration of rainwater below the furrow and better access of plant roots to sub-soil water (Yang et al, 1996;Feng et al, 2001;Ren et al, 2010;Roper et al, 2015) and improvement in growth and yield of various crops under furrow sowing compared with flat planting has been declared in many reports (Blackwell, 1993;Wang et al, 2011;Quanqi et al, 2012;Lian et al, 2016;Li et al, 2018).…”
Section: Seed Yieldmentioning
confidence: 99%
“…The role of tillage in cropping systems has declined significantly with the adoption of conservation cropping systems. While primary tillage operations, such as moldboard plowing, disking, and rototilling (rotary hoeing) are not routinely used, these techniques may be implemented for strategic weed control and soil amelioration purposes in conservation cropping systems (Davies et al 2013;Hobbs et al 2008;Norsworthy et al 2012;Roper et al 2015). Considering the diversity of operations, implement setups, operator techniques, soil characteristics, and tractor conditions, values for energy consumption are inherently variable and should be viewed as comparative energy consumption-based ranking of tillage operations.…”
Section: Primary Tillage Treatmentsmentioning
confidence: 99%